Peningkatan Kewaspadaan Hipertensi Melalui Pemeriksaan Tekanan Darah sebagai Deteksi Dini pada Populasi Lanjut Usia di Panti Werda Hana - Wijaya, Christian; Firmansyah, Yohanes; Syarifah, Andini Ghina; Alifia, Tosya Putri; Kurniawan, Junius; Gunaidi, Farell Christian (BADAN PENERBIT STIEPARI PRESS, 2024)
Hypertension is a major cause of morbidity and mortality worldwide, and its prevalence increases with age. Hypertension is a chronic condition characterised by increased arterial blood pressure. In Indonesia, the prevalence of hypertension ranges from 45.9% in people aged 55-64 years to 63.8% in people aged 75 years and over. Hypertension is known as the